Community-based counseling reaches and helps bereaved people living in low-income households. (4th July 2019) - Newsom, Catherine; Stroebe, Margaret S.; Schut, Henk; Wilson, Stewart; Birrell, John; Moerbeek, Mirjam; Eisma, Maarten C.
Abstract: Objective : Poverty is related to increased grief-related mental health problems, leading some to suggest bereavement counseling should be tailored to income. However, information about accessibility and effectiveness of such counseling programs serving low-income households is scarce. This longitudinal study therefore investigated the association between poverty and complicated grief (CG), and the effectiveness of a community-based bereavement counseling program in serving low-income households. Methods : Two hundred eighty-eight participants (75% female) were enrolled. Loss-related and demographic variables were assessed at baseline. Regression analyses were used to investigate household income as a predictor of CG, and examine bereavement counseling effectiveness by comparing CG symptom change across three household income categories across three time-points: baseline (T1), T1 + 12 months (T2), and T1 + 18 months (T3). Results : Of all participants, 35.8% reported below poverty-threshold income, twice the general population's rate. Multiple regression analysis indicated poverty-threshold income was a predictor of CG symptoms over and above demographic and loss-related characteristics. Three-way interaction analysis detected a significant treatment effect for study condition across time, but no differences in treatment effects across income. Conclusion : Lower household income was associated with higher CG symptoms. Since income did not predict differential treatment response, community-based bereavement counseling appeared no less efficacious for members of low-income households. Clinical or methodological significance of this article : While previous research has indicated low income may be a risk factor for mental health problems after bereavement, and it has therefore been suggested bereavement counseling should be tailored to income, no study to date has investigated the need for such tailoring. This controlled, longitudinal treatment study fills this gap in knowledge. Main findings are that low income is a key predictor of complicated grief symptoms. The study also shows that the effectiveness of one-to-one bereavement counseling does not appear to differ according to income level.